Estimation of the forces acting on the tibiofemoral joint during knee extension exercises performed on an open kinetic chain strength-training machine - Jefferson Fagundes Loss; Joelly Mahnic de Toledo; Felipe Pivetta Carpes; Rodrigo Rico Bini (Universidade Federal de Santa Catarina, 2008)
The objectives of this study were to: (1) evaluate the resistive torque of an open kinetic chain strength-training machine for performing knee extensions, and (2) perform an analysis estimating internal forces in the tibiofemoral joint. During a fi rst phase of the study, measurements were taken of the machine under analysis (external forces), and then calculations were performed to estimate forces on the lower limb (internal forces). Equations were defi ned to calculate human force (HF), and the moment of muscular force (MMF). Perpendicular muscular force (MFp) and joint force (JFp), axial muscular force (MF") and joint force (JF"), and total muscular force (MF) and joint force (JF) were all calculated. Five knee angles were analyzed (zero, 30, 45, 60, and 90 degrees). A reduction was observed in HF at higher knee angles, while MF and JF also increased at the same time. HF was always lower than the load selected on the machine, which indicates a reduced overload imposed by the machine. The reduction observed in MFp and JFp at higher knee angles indicates a lower tendency to shear the tibia in relation to the femur. At the same time, there was an increase in JF" due to higher MF". The biomechanical model proposed in this study has shown itself adequate for the day-to-day needs of professionals who supervise orient strength training. resumo Os objetivos do presente estudo foram: (1) avaliar o torque de resistência (TR) de uma máquina de musculação para a realização do exercício de extensão dos joelhos em cadeia cinética aberta e (2) realizar um ensaio teórico a partir do comportamento do TR com o intuito de estimar as forças internas na articulação tíbio-femoral. O estudo foi realizado em dois momentos: (1) medições da máquina utilizada e (2) estimativa das forças externas (na máquina) e internas (no membro inferior). Foram utilizadas equações baseadas em um modelo mecânico bi-dimensional para o cálculo das componentes perpendiculares e axiais da força muscular (FMp e FM", respectivamente) e da força articular (FAp e FA", respectivamente), assim como de suas resultantes (forças muscular, FM; articular, FA e humana, FH). As variáveis foram mensuradas em cinco ângulos de fl exão do joelho (zero, 30, 45, 60 e 90 graus). Observou-se uma redução da FH com o aumento do ângulo de fl exão do joelho, enquanto FM e FA apresentam aumento. O valor da FH apresentou-se sempre menor ao valor da força resistiva (FR), indicando que a máquina reduz a sobrecarga imposta ao executante. Observa-se uma redução da FMp e FAp nos maiores ângulos de fl exão do joelho, indicando uma redução da força de cisalhamento anterior da tíbia sobre o fêmur. Percebeu-se um aumento da FA", devido ao aumento de FM", principalmente de 45 a 90 graus.